Women's aggressive fantasies : a post-Jungian exploration of self-hatred, love and agency - Austin, Sue. (London ; New York : Routledge, 2005)
Drawing together apparently disparate strands of theory from feminism, critical psychology, contemporary psychoanalysis and post-Jungian thought, this books succeeds in providing a new insight into the phenomenon of female violence and aggression.
Chapter 1 A di.
Includes bibliographical references (pages 251-258) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Women -- Psychology; Aggressiveness; Fantasy; Hate; Love; Fantasy literature; Fantasy; Women -- psychology; Aggression; Aggression -- psychology; Hate; Love; Femmes -- Psychologie; Agressivité.; Fantasmes; Haine; Amour; Littérature fantastique; fantasies (visual works); fantasies (literary genre); hate; fantasy (imagination); love (emotion); PSYCHOLOGY -- Human Sexuality; Love; Hate; Fantasy; Aggressiveness; Women -- Psychology; Electronic book; Electronic books